Early 2016/17 vaccine effectiveness estimates against influenza A(H3N2): I-MOVE multicentre case control studies at primary care and hospital levels in Europe - Kissling, Esther (2018)
I-MOVE/I-MOVE+ study team: Portugal - Baltazar Nunes, Ausenda Machado, Ana Paula Rodrigues, Verónica Gomez, Irina Kislaya, Mafalda Sousa Uva (Departamento de Epidemiologia, Instituto Nacional de Saúde Doutor Ricardo Jorge); Raquel Guiomar, Pedro Pechirra, Paula Cristóvão, Patrícia Conde, Inês Costa (Departamento de Doenças Infeciosas, Instituto Nacional de Saúde Doutor Ricardo Jorge).